Immune multistage evolutionary programming (IMEP) for optimal load shedding approach for loss minimization / Muhammad Faris Baharuddin - Baharuddin, Muhammad Faris (2014)
Optimal Load Shedding (OLS) is one of the way to operate, planning and security in power system. The process by which people use electric power handling power shortage is load shedding. In power systems, many method can be choose in order to solve a problem.